2020
DOI: 10.1038/s41598-020-63100-w
|View full text |Cite
|
Sign up to set email alerts
|

Founder BRCA1/BRCA2/PALB2 pathogenic variants in French-Canadian breast cancer cases and controls

Abstract: Inherited germline pathogenic variants are responsible for ~5% of breast cancer globally. Through rapid expansion and isolation since immigration in the early 17 th century, french canadians are a relatively genetically homogenous founder population and therefore represent a unique demographic for genetic contributions to disease. to date, twenty variants in BRCA1, BRCA2, and PALB2 that predispose families to breast and ovarian cancer have been identified as recurring in the French-Canadian founder population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Further analysis of other members of our cancer family showed only one of five other carriers was affected by BC (unpublished data). This case is from the French Canadian population and carries a pathogenic variant in BRCA2 c.8537_8538delAG; p.Glu2846GlyfsTer22 known to be a founder pathogenic variant as reported by our group and others [84][85][86][87][88][89][90][91][92][93].…”
Section: Carriers Of a Bard1 Variant And A Pathogenic Variant In A Knsupporting
confidence: 52%
“…Further analysis of other members of our cancer family showed only one of five other carriers was affected by BC (unpublished data). This case is from the French Canadian population and carries a pathogenic variant in BRCA2 c.8537_8538delAG; p.Glu2846GlyfsTer22 known to be a founder pathogenic variant as reported by our group and others [84][85][86][87][88][89][90][91][92][93].…”
Section: Carriers Of a Bard1 Variant And A Pathogenic Variant In A Knsupporting
confidence: 52%
“…GO, Gene Ontology; DEGs, differentially expressed genes; CEGs, co-expressed genes; KEGG, Kyoto Encyclopedia of Genes and Genomes BAK1, BRCA2, CDK4, GRB2, HRAS, PIK3R3, and POLK) were associated with the breast cancer pathway (ID: hsa05224), even though this pathway is not in the top 30 KEGG signaling pathways. Eight of these genes (except WNT2, GADD45B, FZD2, WNT7B, POLK, and PIK3R3) have been extensively studied in breast cancer [44][45][46][47][48][49]. Our DO analysis indicated that these genes are closely associated with myeloma, bone marrow cancer, renal cell carcinoma, ovarian cancer, and other cancer types.…”
Section: Discussionmentioning
confidence: 81%
“…The average age of diagnosis was 44.6 years (range 22-65) and 43.7 years (range 18-65) for HBC and HBOC families, respectively. Sporadic BC cases were diagnosed with invasive BC before the age of 70 (average = 52.7, range 25-69) 131 . We cannot exclude the possibility that some cases occurred in more than one study group: based on RRCancer biobanking sample number, OC cases from at least 13 families were also found in pedigrees from BC cases that were genotyped from the familial HBOC study group.…”
Section: Methodsmentioning
confidence: 99%
“…Where normal DNA was no longer available from the study case, genomic DNA extracted from the tumor (if available) was provided by the RRCancer biobank for genotyping. PBL DNA from sporadic BC cases were genotyped using Sequenom® iPLEX® Gold Technology at the MGC 131 . Samples that were removed from the analysis were due to poor DNA quality (n=30), duplication (n=1), or were from cases exceeding age limit criteria (70 years or older when diagnosed with first invasive BC; n=2).…”
Section: Methodsmentioning
confidence: 99%